1999
DOI: 10.1191/096120399678840882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti-CD4 antibodies on the release of IL-6 and TNF-α in whole blood samples from patients with systemic lupus erythematosus

Abstract: Anti-CD4 antibodies have been recently introduced into the therapy of various autoimmune diseases, among them systemic lupus erythematosus (SLE). Their modes of action are not yet fully understood. Interference with cytokine release may be one possible mechanism. Therefore, the effects of anti-CD4 antibodies on the cytokine release of IL-6 (interleukin-6) and TNF-alpha (tumor necrosis factor alpha) were investigated in a whole blood culture system. Basal and phytohemagglutin/lipopolysaccharide (PHA/LPS)-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
11
0
3
Order By: Relevance
“…Brink et al (17) reported that even low doses of steroids inhibit cytokine synthesis in SLE patients. Similarly, in the present study, the effects of glucocorticoids on serum IL-9 levels and CD4 + IL-9 + T cells in SLE patients were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Brink et al (17) reported that even low doses of steroids inhibit cytokine synthesis in SLE patients. Similarly, in the present study, the effects of glucocorticoids on serum IL-9 levels and CD4 + IL-9 + T cells in SLE patients were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…14 ± 18 They also seem to have effects on peroxisomal proliferating activating receptors (PPARs) and in particular the alpha subgroup of these receptors. 16,17,19 This action of statins results in a decrease in cytokine production by endothelial cells, eg interleukin- 6,20 and has been demonstrated to identify patients who bene®t from statin therapy in clinical trials in having co-associated falls in plasma CRP and cardiac events. 21 Whether all statins have similar actions, particularly in their effects on coagulation, is controversial.…”
Section: The Actions Of Lipid-lowering Drugsmentioning
confidence: 99%
“…This information is important for an appreciation of our results, since all patients were receiving low to moderate doses of prednisone. Brink et al reported that even low doses of steroids can inhibit cytokine synthesis in patients with SLE 21. In another study, Swaak et al observed that patients with SLE taking prednisone at a dose of <15 mg/day showed a reduction in “ ex-viv o” production of IL-6 and TNF-α 22.…”
Section: Discussionmentioning
confidence: 99%